A Concise Synthesis of a Key Azabicyclo[2.1.1]hexane Building Block for N-Heteroaryl Indazole LRRK2 Kinase Inhibitors - Candito, David A.; Simov, Vladimir; Liu, Ping; Ardolino, Michael J.; Martinot, Theodore; Lyons, Thomas; Qi, Ji; Yin, Jingjun; Hao, Jinglai; Hu, Bin; Chen, Meng; Zhang, Jun; Lam, Yu-hong; Fuller, Peter H.; Ellis, J. Michael; Maddess, Matthew (Synlett, 2025)
Increasing the fraction of sp3 character in lead compounds has been shown to increase their drug-likeness by improving their potency, selectivity, and physicochemical properties. Azabicyclo[2.1.1]hexanes have recently garnered much interest in the synthetic community as pyrrolidine analogues for their interesting biological properties and stereoelectronic effects. During the course of our optimization of N-heteroaryl LRRK2 inhibitors, we discovered that this unique bicyclic system leads to improvements in solubility and metabolic clearance. Herein, we outline a match-pair analysis showcasing the broad impact of this unique azabicyclo[2.1.1]hexane system on key drug-like properties, as well as a concise and scalable synthesis of this building block, featuring an intramolecular cyclization to forge a strained amide bond.
Keywords: amides; bicyclic compounds; drugs; heterocycles; lactams; medicinal chemistry